A Community Study of the Risk Factors and Perceived Susceptibility to Kidney Disease Risk in Lagos State, South West Nigeria (African Journal of Biomedical Research, 2022)
Kidney disease (KD) is one of the major public health threats with rising incidence and prevalence rates. Knowledge and perceived risk increase the perception of being susceptible, leading to adoption of behavioural modifications. The objective was to evaluate the knowledge of KD risk factors and perceived susceptibility as well as predictors of KD risk in Lagos State, Nigeria. This was a cross-sectional study conducted in Lagos State, South-western Nigeria. A pretested structured questionnaire was used to draw information from 1171 male and female residents aged ≥ 18 years on socio-demography, knowledge and perceived susceptibility to KD risk. Percentages, frequencies, Chi-square, binary and multinomial logistic regression models were used, with a significance of p
Keywords: kidney diseases; knowledge; perceived susceptibility; risk factors